Optimisation of production activities on individual agricultural holdings in the frame of different direct payments options - Jaka ŽGAJNAR; Emil ERJAVEC; Stane KAVČIČ (Acta Agriculturae Slovenica)
Linear programming model has been developed and applied to the hypothetical agricultural holding in the hilly part of Slovenia in order to find optimal production plans by maximizing total gross margins. The model covers especially those sectors of Slovenian agriculture, for which the most drastic changes due to the actual reform of CAP in the field of direct payments – in Slovenia implemented in 2007 – are anticipated. On the basis of developed model the economic impacts of CAP reform and importance of agri-environmental measures have been evaluated. Model results lead to the conclusion that the reform will have the most unfavorable impacts for agricultural holdings with intensive production practice, especially those with animal production activities which are under the standard scheme eligible for relatively high production coupled direct payments (up to 70% of achieved total gross margin). Negative impacts of the reform can be mitigated by combining different production activities and technologies. Economic results markedly improve (up to 28%) if farming management complies with agri-environmental measures.